Taxonomy and chorology of Corbichonia (Lophiocarpaceae s.l.) with further description of a new species from Southern Africa - Sukhorukov, Alexander P.; Kushunina, Maria (Phytotaxa, 2015)
A re-examination of the herbarium material has allowed to describe a new species, Corbichonia exellii, occurring in Southern Africa (Angola, Namibia and South Africa). C. exellii represents the third species in the genus. Morphological differences between all three Corbichonia species (C. decumbens, C. rubriviolacea, and C. exellii) are provided. The description of the genus is defined using the newly discovered characters (reproductive features). The taxonomy of all Corbichonia species (synonyms included) is provided, as well as maps for all species. The lectotypes of Orygia decumbens (basionym of Corbichonia decumbens) and O. mucronata (synonym of C. decumbens) are designated on specimens preserved, respectively, at BM and K. The genus Corbichonia, recently placed in Lophiocarpaceae, is markedly different from the core genus Lophiocarpus on the basis of embryological, morphological and carpological characters, and deserves further investigation concerning its taxonomic status.